A whole process resilience management practice in coastal engineering - Zhou, Yingtao; Jiang, Chenhui; Jiang, Yuanshu; Zhu, Yu; Jin, Yan; Wang, Xian; Feng, Xi; Feng, Weibing (Frontiers in Marine Science, 2025)
Coastal zones are crucial for protecting land from marine disasters, but they are increasingly threatened by erosion caused by storms and rising sea levels. Urban coastal resilience engineering is a multidisciplinary practice that seeks to enhance disaster prevention capabilities and resilience along urban coastlines. This process requires a comprehensive assessment based on the current conditions and regional characteristics, followed by tailored planning and design strategies. Previous research has mainly focused on individual coastline types, utilizing observations or numerical models for analysis. However, it often lacks a comprehensive approach that integrates planning, design, and assessment. This paper proposes a project life cycle management method for resilient coastal zone engineering, including design and construction within a layout planning framework. The proposed scheme incorporates small-scale numerical simulations for the evaluation and employs high-precision remote sensing data collected over different construction periods to assess the coastline’s transformations during the process of construction. Additionally, a hierarchical evaluation index system was established using the analytic hierarchy process to assess project outcomes after completion. The Haidian River-Haikou Bay Coastal Resilience Project serves as a case study and this study thoroughly evaluates the project’s impact on the vitality and resilience of the coastal zones. This research provides valuable insights and practical guidance for future coastal resilience restoration efforts in diverse urban contexts.